Enhancing the development of students’ Islamic identity in Islamic higher education - Husein, Saddam; Nik Abdullah, Nik Md. Saiful Azizi; Al-Hidabi, Dawood Abdulmalek Yahya (Universitas Muhammadiyah Malang, 2022)
Modern globalization with the spread of western culture and values obviously challenges the Islamic identity of Muslim youth which makes them following the alien culture and leave the Islamic one. The role of Islamic higher education is considered as one of the most crucial agent for countering this challenges. Therefore, the present study aims to explore the role of Institute for Islamic Studies and Practice (LPPI) UMY in developing the students’ Islamic identity. The study employed case study design using qualitative approach to capture the real-life context of LPPI UMY in playing its role. Through purposive sampling, head of LPPI UMY was selected as the informant in the study considering his role and experiences leading this institution for about ten years. The data were analyzed through thematic analysis to emphasize on pinpointing, examining, and recording patterns (or "themes") from the verbatim transcribed data. The findings revealed that LPPI UMY as an institution that mandated by university to manage and develop Al-Islam and Kemuhammadiyahan (AIK) for the entire academic community in UMY plays its role in developing the Students’ Islamic identity through two major programs; Learning and Guidance Programs. Learning programs are conducted as courses inside the faculty’s curricula and consists of four courses, AIK 1, 2, 3, and AIK 4. Guidance programs on the other hands are conducted as extracurricular and formulated in the form of The Scheme of Character Building through some stages of Islamic activities, as well as supported by other program such as Ramadhan activities.